Zawód specjalisty ds. rachunkowości zarządczej w perspektywie etycznej - Kalinowska, Katarzyna; Kalinowski, Marcin (Annales. Etyka w Życiu Gospodarczym, 2014)
Increasing market competitiveness has brought about changes in enterprise management. There was a demand for an increase in the quality and quantity of information needed for operational and strategic management procedures. With the increasing demand for the desired cross-section of information necessary for an accounting system, in addition to the financial accounting responsible for generating financial information, management accounting was established. The purpose of this article is to seek answers to the question about how the professional ethics of management accountants are related to the nature and specifics of carrying out their professional duties.